Reinterpretation of Salodik Group Performance Based on Facies and Diagenesis Approaches to Classify Reservoir Quality - Jambak, Moeh. Ali; Ibrahim, Ivan; Harnest, Billy; Irano, Teddy; Prabawa, Gusti; Luthfi, Ramadhan; Prasetyo, Ardyand Budi (Geological Agency, 2024)
An integrated study of several methods to characterize a carbonate reservoir provides a comprehensive result on carbonate facies and diagenesis. Therefore, a study on the Tertiary carbonate reservoir at the East Arm of Sulawesi area, Banggai – Sula Basin, is intended to determine the Salodik Group carbonate reservoir facies and diagenesis. Moreover, the purpose of this study is to determine the intensity and implication of syn-depositional or post-depositional processes, and to provide the reservoir final properties values, such as porosity and permeability to classify the reservoir quality. The methods of the study are based on carbonate fieldwork mapping to obtain samples on distributed traverses. Further analyses are the laboratory works to determine facies and diagenesis features on a more detailed scale. This study shows several facies, dominantly classified into reefal packstone, planktonic foraminifera packstone-wackestone, large foram packstone-mudstone, skeletal packstone-wackestone, planktonic-large foraminifera packstone-wackestone, and large foraminifera-red algae packstone. The dominant diagenesis processes are cementation and dissolution. Moreover, meteoric vadose and meteoric phreatic are predominantly the main diagenesis environment of Salodik Group formations. Furthermore, the dominant diagenesis stage is Eogenetic. The post-depositional process or the diagenetic processes, provides a more significant impact on carbonate reservoir properties than the syn-depositional process as shown on lithofacies texture. However, in general, from the younger to the oldest formation of Salodik Group, this shows a decreasing trend of reservoir properties due to the dominantcementation process in the oldest formation. Overall, the reservoir quality referring to porosity value is classified as negligible to excellent. While, based on permeability data, it is classified as the tight to good reservoir.